Ecological understanding the nature of theory and the theory of nature - Pickett, Steward T., 1950-; Kolasa, Jurek; Jones, Clive G. (Amsterdam ; Boston : Elsevier/Academic Press, 2007)
This widely anticipated revision of the groundbreaking book, Ecological Understanding, updates this crucial sourcebook of contemporary philosophical insights for practicing ecologists and graduate students in ecology and environmental studies. The second edition contains new ecological examples, an expanded array of conceptual diagrams and illustrations, new text boxes summarizing important points or defining key terms, and new reference to philosophical issues and controversies. Although the first edition was recognized for its clarity, this revision takes the opportunity to make the exposition of complex topics still clearer to readers without a philosophical background. Readers will gain an understanding of the goals of science, the structure of theory, the kinds of theory relevant to ecology, the way that theory changes, what constitutes objectivity in contemporary science, and the role of paradigms and frameworks for synthesis within ecology and in integration with other disciplines. Finally, how theory can inform and anchor the public use of ecological knowledge in civic debates is laid out. This new edition refines the understanding of how the structure and change of theory can improve the growth and application of one of the 21st centurys key sciences. Explains the philosophical basis of ecology in plain English Contains chapter overviews and summaries Text boxes highlight key points, examples, or controversies Diagrams explain structure and development of theory, and integration Evaluates and relates paradgims in ecology Illustrates philosophical issues with classic and new ecological research.
Foreword -- Preface -- Part I: Advancing the Discipline and Enhancing Applications -- Ch. 1 Integration in Ecology -- Ch. 2 Understanding in Ecology -- Part II: The Nature of Theory -- Ch. 3 The Anatomy of Theory -- Ch. 4 The Ontogeny of Theory -- Ch. 5 The Taxonomy of Theory -- Part III: From Theory to Integration and Application -- Ch. 6 Fundamental Questions:Changes in Understanding -- Ch. 7 Integration and Synthesis -- Part IV: Theory and Its Environment -- Ch. 8 Constraint and Objectivity in Ecological Integration -- Ch. 9 Ecological Understanding and the Public.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Ecology -- Philosophy; Ecology -- Methodology; Electronic books